2013
DOI: 10.1210/jc.2012-3937
|View full text |Cite|
|
Sign up to set email alerts
|

Development of p21 Activated Kinase-Targeted Multikinase Inhibitors That Inhibit Thyroid Cancer Cell Migration

Abstract: We have developed 2 new multikinase inhibitors with anti-PAK activity that may serve as scaffolds for further compound development targeting this progression-related thyroid cancer target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Numerous studies showed that phosphorylated p21-activated kinase 1 (PAK1) is involved in cell migration (26)(27)(28)(29). Because PAK1 is considered a key downstream effector of Rac1 signal pathway, we sought to determine the role of PIAS3 in PAK1 activation in RA FLSs.…”
Section: Pias3 Knockdown Decreases Tnf-a-induced Activation Of Pak1 Amentioning
confidence: 99%
“…Numerous studies showed that phosphorylated p21-activated kinase 1 (PAK1) is involved in cell migration (26)(27)(28)(29). Because PAK1 is considered a key downstream effector of Rac1 signal pathway, we sought to determine the role of PIAS3 in PAK1 activation in RA FLSs.…”
Section: Pias3 Knockdown Decreases Tnf-a-induced Activation Of Pak1 Amentioning
confidence: 99%
“…Currently, recent studies have demonstrated that the inhibition of PAKs might be beneficial in several human conditions such as Neurofibromatosis Type 2 [135,142], fragile X syndrome [136], thyroid cancer [143], other cancers [144,145], and ulcerative colitis [9]. Yet, in spite of the large body of evidence that PAK1/2 regulate NADPH oxidase activity, no PAK inhibitors have been implicated in the regulation of inflammation.…”
Section: Paks As a Pharmacological Targetmentioning
confidence: 99%
“…Binding of AR12 is located in the ATP binding pocket of PAK and by using computer modeling AR12 was structurally altered to reduce its PDK1 inhibition and enhance its PAK inhibition. These alterations resulted in a panel of 17 compounds, among them cpd8 (PI-8) and cpd15 (PI-15) (26). Two compounds, cpd4 and cpd15, reduced cell viability and cell migration in thyroid cancer cells, and constitutively active PAK1 rescued the anti-migration effect in thyroid cancer cells indicating that both compounds inhibit PAK activation (26).…”
Section: Introductionmentioning
confidence: 99%
“…These alterations resulted in a panel of 17 compounds, among them cpd8 (PI-8) and cpd15 (PI-15) (26). Two compounds, cpd4 and cpd15, reduced cell viability and cell migration in thyroid cancer cells, and constitutively active PAK1 rescued the anti-migration effect in thyroid cancer cells indicating that both compounds inhibit PAK activation (26). These same studies confirmed that both compounds decreased PAK phosphorylation.…”
Section: Introductionmentioning
confidence: 99%